Clinical safety assessment of the Halcyon system. Issue 10 (20th August 2019) - Pawlicki, Todd; Atwood, Todd; McConnell, Kristen; Kim, Gwe-Ya
Abstract : Purpose: The Halcyon consists of precommissioned linear accelerator and treatment planning algorithms that were designed to simplify the acceptance, commissioning, and clinical workflow for image‐guided intensity‐modulated radiotherapy. The purpose of this work was to perform a comprehensive safety assessment for the clinical use of the Halcyon. Methods: Systems‐Theoretic Process Analysis was used as the safety assessment tool. As part of the analysis, a number of control loops and control actions are created to describe system function. Safety is assessed by determining unsafe control actions and a corresponding list of causal scenarios that leads to accidents. The scope of the analysis was from the acceptance of the Halcyon to routine patient treatments. All aspects of treating patients were considered including the roles of physicians, physicists, dosimetrists, and therapists. The analysis was completed by four physicists with input from other members of the radiation therapy team. The causal scenarios were summarized using the causality categories from the consensus recommendations for incident learning database structures in radiation oncology (Med Phys, Vol. 39, No. 12, Dec 2012). Results: Twenty‐three (23) control loops containing 52 control actions were created for the clinical use of the Halcyon. One hundred forty‐four (144) unsafe control actions were identified with 385 associated causal scenarios. Twenty‐seven percent (27%) of the causal scenarios were related to equipment technical issues, while 73% of the causal scenarios were predominantly related to procedural issues, human behavior, and organizational management. Conclusions: For routine clinical use of closed or largely automated radiation therapy equipment, the majority of safety concerns is related to nontechnical issues. The Halcyon and other similar systems may present opportunities to streamline, reduce, or eliminate some traditional equipment commissioning and routine quality assurance activities in exchange for an increased focus on issues related to organizational management, procedures, and human behavior.